Participative spatial planning on marginalised campuses during transformational processes - Smit, Emmie (University of the Free State, 2016)
Abstract not available
Keywords: Satellite campus; Rural and remote campus; Branch campus; Distance campus; Northern tradition; Southern tradition; Dissertation (M.U.R.P. (Urban and Regional Planning))--University of the Free State, 2016